Geophysical Approach for Water Seepage Study in Near Surface Assessment - T Adeeko; N.M Muztaza; M.T Zakaria; N.A Ismail; N Samsudin; A.A Bery; F. Ahmad (International Association of Lowland Technology, 2020)
Water seepage at urban area will affect the hydraulicconductivity and shear strength of soil that may causesubsurface problems such as landslides, sinkholes, cavities,ground subsidence and hazard to buildings. To delineateseepage pathways, geophysical data will be acquired. A studyhas been conducted at Penang to study the saturated zone,analyze the water flow directions and intensities to determinethe causes of localized near surface problems by using the 2-Dresistivity and self-potential (SP) methods. Five 2-D resistivitysurvey lines with minimum of 0.5 m electrode spacing wereexecuted using Pole-dipole array. The flow directions andintensities of the water were determined using self-potential(SP) method with interval spacing of 1 m. The inversion resultsshow the low resistivity value (1-100 Ωm) was dominant at thestudy area which was interpret as saturated zone. Resistivityvalue of 100-800 Ωm was interpret as alluvium. The resultdisplay by self-potential contour map shows the water flow fromhigher self-potential value (38 mV) towards the lower selfpotentialvalue (-22 mV) that is flow from west to east, which arerelated to seepage flow patterns, negative SP anomalies wererelated with subsurface seepage flow paths (recharge zone) andpositive SP anomalies were related with areas of seepageoutflow (discharge zone). Therefore, the two results have matchand show good correlation in water seepage investigation,which validates the results